Rekayasa Digital Situng KPU untuk Mengantisipasi Kecurangan Elit Parpol (Studi di KPU Kota Bandar Lampung) - Narita Hayunanda; Tabah Maryanah; Maulana Mukhlis; Hertanto Hertanto (Journal on Education, 2023)
The formula for the most votes in determining the list of candidates who win seats in each constituency makes all candidates have the same opportunity to be elected. Therefore, it is not uncommon for elite political parties to be unable to compete with external candidates who are recruited just before the election. Political party elites who are not elected have the potential to commit fraud. With the party's infrastructure, the political party elites who are not elected have the potential to change vote acquisition. To anticipate this fraud, the KPU carried out Digital Engineering by implementing the Vote Counting Information System (Situng). Through Sitting, the results of the legislative candidates' votes will be published quickly to the public. That way, the public can participate in exercising control over the recapitulation stages of counting the votes acquired by political parties and their candidates. This study uses a qualitative descriptive research method. Data was obtained and processed to be used as material for conducting interviews with informants related to Sitting. The research location is at KPU Bandar Lampung City. The conclusion of this study is that the Open Proportional System with the most votes has resulted in the failure of a number of political party elites in Bandar Lampung City to sit in parliament. Digital engineering in the form of implementing Situng KPU is an anticipation of the potential for fraud committed by political party elites.